Rethinking the relationship between desiccation-tolerant vascular plants and water deficit - Bondi, Luiz; Prado, Beatriz; de Paula, Luiza F. A.; Rosado, Bruno H. P.; Porembski, Stefan (Plant ecology & diversity, 2024)
Water deficit is one of the main drivers of plant mortality and is projected to be more critical owing to climate change. Because desiccation-tolerant vascular plants (DT plants) can cope with water deficit, the paradigm emerges of their strong association with and restricted occurrence to locations characterised by water deficit conditions. However, this paradigm is not supported by earlier studies, hampering our understanding of the species - environment relationships and the vulnerability of DT plants to climate change. We tested this paradigm and provide an evaluation of the vulnerability of DT plants to climate change. We estimated the diversity and distribution of DT plants along water deficit gradients and assessed species vulnerability to climate change from a climatic perspective and over broad phylogenetic and macroecological scales. The diversity and distribution of DT plants were neither associated with, nor restricted to, locations characterised by water deficits. Species with narrow niche breadth and poikilochlorophylly might be the most vulnerable to climate change. Our findings suggest that the desiccation events DT plants undergo are promoted by topo-edaphic conditions rather than by climate. We suggest that ecologically restricted species and those with a poikilochlorophyllous strategy should be prioritised for conservation.